EFEKTIVITAS BUKU AJAR STATISTIKA NON PARAMETRIK UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA - Taqwa, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this study was to create effective teaching materials that improve conceptual understanding. The research theme was to develop textbooks using Thiagarajan's 4D model: definition, design, development, and distribution. The research was conducted at the Mathematics Education Study Program, Khairun University. The textbook validity sheet and conceptual understanding test were used as research instruments. Findings: (1) high category obtained for content validity and reliability of textbooks; (2) medium category obtained for average increase in students' conceptual understanding scores. Non-parametric statistics textbooks with relevant and effective criteria improve conceptual understanding of Khairun University students.